Taxonomy, Ontogenesis and Evolutionary Relationships of the Algae-Bearing Ciliate Bourlandella viridis (Kahl, 1932) comb. nov., With Establishment of a New Genus and New Family (Protista, Ciliophora, Hypotrichia) - Song, Wenya; Zhang, Tengyue; Zhang, Xue; Warren, Alan; Song, Weibo; Zhao, Yan; Luo, Xiaotian (Frontiers in Microbiology, 2021)
Hypotrichs are the most complex and highly differentiated ciliate lineage and have great potential for evolutionary novelties. Hypotrichid systematic problems are mainly due to discordance between the morphological and genetic data. Species with morphologies that are characteristic of more than one higher rank taxon are probably a major contributing factor to these conflicts. The present study describes a Chinese population of a poorly known organism with numerous endosymbiotic zoochlorellae, the morphology of which corresponds well with the type population of Limnoholosticha viridis (Kahl, 1932) Li et al. 2017. Newly obtained information shows this species has a zigzag midventral cirral pattern that is diagnostic of urostylids, whereas the dorsal ciliature shares features (presence of dorsomarginal kinety and dorsal kinety 3 fragmentation) that are typical of oxytrichids. Molecular phylogenetic analyses reveal a close relationship with oxytrichids. An integrative approach combining morphological, morphogenetic, phylogenetic and ecological analyses indicates that L. viridis represents a new genus and new family which might be an intermediate form between uorstylids and dorsomarginalians. Thus, Bourlandellidae fam. nov. and Bourlandella gen. nov. are here established. Lastly, we speculate that phenotypic convergence and mixtrophy might confer on Bourlandella viridis the ability to adapt to a wide range of environmental conditions.